The Application of Islamic Legal Maxim of Blocking Evils is Precedenced than Taking Benefits in Cryptocurrency Market: Evidence from Treynor and Jensen Method - Ghoni, Muhammad Abdul; Syafei, Ade Wirman; Ariza, Kemal (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2022)
This practical analysis and investigated research of the performing cryptocurrency investment during the January 2019-September 2021 period. This study is evaluating five cryptocurrencies within global Cryptocurencies market. Treynor and Jensen Index are utilized to measure each cryptocurrencies operation in the crypto currencies market. Moreover, the analysis of Islamic Legal maxim of blocking evils is precedenced than taking benefits in Cryptocurrency Market is applied. The Treynor and Jensen Index analysis approach is used to evaluate performance among the five cryptocurrencies, namely; Bitcoin (BTC), Ethereum (ETH), Binance Coin (BNB), Tether (USDT) and Cardano (ADA . The results of Treynor index indicate cryptocurrencies, namely; Tether (USDT), Ethereum (ETH), Cardano (ADA) assets carried the has a positive value means the performance of cryptocurrency is good as compare other Cryptocurrencies. However, the results of Jensen index show the four crypto assets, namely; Bitcoin (BTC), Ethereum (ETH), Tether (USDT), Cardano (ADA) have a negative Jensen value, these indicates the cryptocurrencies have low returns. The finding of the result from the analysis of the of Islamic Legal maxim of preventing evils is better than attracting benefits suggest to avoid cryptocurrency investment is priority rather than taking benefit from cryptocurrency investment